Kesiapan Calon Guru dalam Pengimplementasian Standar Penilaian Pendidikan Kurikulum 2013 Edisi Revisi (Studi Kasus Mahasiswa STKIP Darussalam Cilacap Semester 7 Tahun Akademik 2018/2019) - Wulandari, Mey Prihandani (Jurnal Pancar, 2018)
The purpose of this study is to identify the preparation made by prospective teachers in implementing the Assessment Standard in Education for the revised edition of the curricula 2013 which is a case study of STKIP Darussalam Cilacap students in the 7th semester of Academic Year 2018/2019. This research is quantitative research. The research subjects were 74 prospective teachers who were STKIP Darussalam Cilacap students in the 7th semester of the academic year 2018/2019. Data were collected through questionnaire. The data analysis technique using descriptive statistical analysis. The results of this study indicate that: (1) the preparation made by prospective teachers in implementing the Assessment Standard in Education for the revised edition of the curricula 2013 is in the good category as many as 49 prospective teachers (66%) already know Permendikbud Number 23 Year 2016. (2) understanding of prospective teachers to assessment approach still needs to be improved. (3) the majority of prospective teachers know well all forms of assessment. (4) some prospective teachers already have knowledge and skills about the technique of assessing attitudes, knowledge and skills competencies, except for observation, performance, project, product and portfolio assessment techniques. (5) Most of the prospective teachers still need to be improved in knowledge and skills about the form of the report on the results of the assessment. Recommended of this study is that prospective teachers need additional training about the Assessment Standard in Education for the revised edition of the curricula 2013 before implementing the internship 3 program.